IMPROVING THE TECHNICAL TRAINING OF SPORT DANCERS AT THE SPECIALIZED BASIC TRAINING STAGE - Лисенко, Альберт; Мішин, Максим; Горбенко, Олена; Шкурєєв, Кирило; Широковська, Олександра (SWorldJournal, 2025)
The article discusses the improvement of the technical training of sport dancers at the stage of specialized basic training. Through the analysis of scientific and methodological literature, a number of classifications used in sport dances were identified